1997
DOI: 10.1016/s0006-3495(97)78066-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyethyleneglycol-phospholipids on aggregate structure in preparations of small unilamellar liposomes

Abstract: Phospholipids with covalently attached poly(ethylene glycol) (PEG lipids) are commonly used for the preparation of long circulating liposomes. Although it is well known that lipid/PEG-lipid mixed micelles may form above a certain critical concentration of PEG-lipid, little is known about the effects of PEG-lipids on liposome structure and leakage at submicellar concentrations. In this study we have used cryogenic transmission electron microscopy to investigate the effect of PEG(2000)-PE on aggregate structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 25 publications
9
163
2
Order By: Relevance
“…Their presence, however, may seriously influence the aggregate structure. High concentrations of PEG-lipids will, in most phospholipid/PEG-lipid mixtures, induce the formation of mixed spherical micelles [4][5][6][7][8][9][10][11]. Previous studies have shown that two fundamentally different types of mixed micellar aggregates may form at intermediate PEG-lipid to lipid ratios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their presence, however, may seriously influence the aggregate structure. High concentrations of PEG-lipids will, in most phospholipid/PEG-lipid mixtures, induce the formation of mixed spherical micelles [4][5][6][7][8][9][10][11]. Previous studies have shown that two fundamentally different types of mixed micellar aggregates may form at intermediate PEG-lipid to lipid ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that two fundamentally different types of mixed micellar aggregates may form at intermediate PEG-lipid to lipid ratios. Depending on the characteristics of the lipid mixture the PEG-lipids induce formation of either long threadlike or discoidal micelles [7,10,12,13]. Threadlike micelles are, for example, commonly observed in PEG-lipid/lipid samples where the lipid is in the liquid crystalline phase, while discs are observed in such mixtures supplemented with cholesterol [7,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from vesicles to open structure and to an intermediate domain in which both vesicles and bilayer coexist were also observed and described for phospholipids/cholesterol/PEG-PE [37] and phospholipid/ Pluronic ® systems [11]. The transition mechanism was explained in terms of vesicle-to-micelle transition [37].…”
Section: Discussionmentioning
confidence: 87%
“…Lipid-anchored PEG stabilizes the liposome and prevents the rapid recognition and consequent uptake of MLs via the mononuclear phagocyte system. [23][24][25] In addition, functionalized derivatives of PEG-lipids can be used for the convenient coupling of targeting sequences to the surface of the liposomes to achieve specific cellular recognition. Here, we have synthesized PEG-coated stealth magnetic liposomes (sMLs) by evaluating two different types of commercially available USPIOs.…”
Section: Introductionmentioning
confidence: 99%